Study On Haematological Parameters In Berari Goat - Kuralkar, Prajakta; Dhenge, S. A.; Kuralkar , S. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Goat rearing is one of the most important sources of income for majority of rural families. Berari is recently recognized as 23rd goat breed of India with accession number INDIA_GOAT_1100_BERARI_0623 (Kuralkar et al., 2013). The Berari goat, a breed of central India (Vidarbha region of Maharashtra), is low yielding prolific meat breed thriving well in tropical wet and dry climate. The significance of determining haematological and biochemical indices of domestic animals has been well documented (Babeker and Elmansoury, 2013). The hematological and biochemical values are very important for evaluation of normal physiological status of animal. No information are available in literature on pertinent values of blood parameters in Berari goats . Considering these facts, the present study was undertaken to determine the normal hematological and biochemical values of Berari goats .